Intraoperative Peritoneal Interleukin-6 Concentration Changes in Relation to the High-Mobility Group Protein B1 and Heat Shock Protein 70 Levels in Children Undergoing Cholecystectomy - Marzena Tylicka; Ewa Matuszczak; Joanna Kamińska; Wojciech Dębek; Beata Modzelewska; Tomasz Kleszczewski; Violetta Dymicka-Piekarska; Joanna Matowicka-Karna; Maria Karpińska; Olga M. Koper-Lenkiewicz (Mediators of Inflammation)
The aim was the evaluation of IL-6 concentration in peritoneal lavage fluid of children which underwent cholecystectomy to ascertain if there is a difference in early inflammatory response depending on the type of surgical approach (open vs. laparoscopy). The analysis of high-mobility group protein B1 (HMGB1) and heat shock protein 70 (HSP70) was performed to find out if the source of IL-6 was related to tissue damage. IL-6 concentration in peritoneal lavage fluid samples, obtained at the beginning and at the end of the laparoscopic (N=23) and open cholecystectomy (N=14), was tested with a routinely used electrochemiluminescence assay. The concentrations of HMGB1 and HSP70 were analyzed with the use of an ELISA method. Statistical analysis was performed using the STATISTICA PL release 12.5 Program. The differences were assessed using the Mann-Whitney U test and Wilcoxon matched pairs test. Correlations were studied by using the Spearman correlation test. Our results demonstrated significant peritoneal lavage fluid IL-6 concentration growth measured at the end of the cholecystectomy as compared to the beginning, regardless of the type of the procedure. IL-6 growth during open cholecystectomy was greater compared to laparoscopic cholecystectomy (62.51-fold vs. 3.19-fold). IL-6 concentration did not correlate with HMGB1 and HSP70, which indicate that the significant growth of this cytokine was not related to mechanical tissue damage due to surgical procedure. A clinical significance of the study could be related to the fact that the evaluation of IL-6 concentration in peritoneal lavage fluid may be useful to assess an early local inflammatory response.